The Interest Rate Should not be Interpreted as a Price - Martin Hellwig (Springer, 2021)
Abstract The paper criticises interpretations of the interest rate as a price. Prices are exchange ratios for different objects; the interest rate is a parameter characterising an intertemporal exchange ratio but is not itself an exchange ratio. Therefore, negative (real) interest rates can arise naturally without policy interventions. Interpretations of the interest rate as a rental rate for capital are shown to be untenable when there are many goods. The paper also sketches the historical background of the discussion, in particular, the English classical economists and Marx, the neoclassical model of Clarke and Wicksell, and Joan Robinson’s criticism of this model.